Hot Spring Gas Geochemical Characteristics and Geological Implications of the Northern Yadong-Gulu Rift in the Tibetan Plateau - Xiaoli Yu; Xiaoli Yu; Zhifu Wei; Gen Wang; Xueyun Ma; Xueyun Ma; Ting Zhang; Hui Yang; Liwu Li; Shixin Zhou; Xianbin Wang (Frontiers in Earth Science, 2022)
To reveal the heat source and its formation mechanism of the northern Yadong-Gulu rift (YGR), we analyzed the helium isotope, carbon isotope (δ13CCO2), and CO2/3He and CH4/3He ratios of hot spring gases for tracing the source of volatiles and discussing their geological significance. The results show the following: helium is mainly derived from the crust, and the radioactive decay of the thicker crust and granites provided more 4He to the low helium isotopes; thermal decomposition of carbonate rocks is the main source of CO2; CH4 may be of organic origin. To sum up, the gas geochemical characteristics of hot springs in the northern YGR indicate that the volatiles are mainly derived from the crust. The crust/mantle heat flow ratios (qc/qm) calculated by helium isotopes cover a range of 0.84–1.48, suggesting that the heat is mainly contributed by the crust. The crustal origin gas and heat flow demonstrates that the heat source beneath the northern YGR is formed by the process of interior crust. Combined with geophysical data, we suggest that the stress heat caused by the collision of the Indo-Eurasian plate and the radiant heating of the crust lead to the heat source (partial melting) and provide heat for thermal activities.